Criminal Law Policy in Tackling Criminal Act of Hoarding Oil Eating Subsidies Statutory Government Number 7 of 2014 Concerning Trade - Elvan Try Budiyanto; Kusno Kusno; Toni Toni (Journal of Social Research, 2022)
Background: The need for basic goods in Indonesia is currently experiencing a crisis, due to the rising prices of basic goods, making it difficult for people to meet their daily needs. Objective: This study aims to find out and analyze consumer protection against hoarding cooking oil staples. As well as knowing and analyzing about the inhibiting factors in overcoming the accumulation of cooking oil. Methods: This research belongs to the normative type of research. So it can be known that based on the rule of law, the hoarding act violates the provisions according to Article 29 of Law Number 7 of 2014 concerning Trade. Result: Consumers should be protected from the hoarding of Cooking Oil Staples. The determination of necessities is carried out based on the allocation of household expenditures nationally for these goods is high, while the determination of important types of goods is carried out based on the strategic nature of national development (Presidential Regulation of the Republic of Indonesia Number 71 of 2015 concerning the Determination and Storage of Basic Necessities and Important Goods). Conclusion: Based on the explanation above, it can be concluded that based on the rule of law, the hoarding act violates the provisions according to Article 29 of Law Number 7 of 2014 concerning Trade.